PERAN SEKOLAH INKLUSI TERHADAP TUMBUH KEMBANG ANAK AUTISME - Fahmi Rieskiana (JEA (Jurnal Edukasi AUD), 2021)
This study aims to determine the role of inclusive schools on the growth and development of children with autism. This research is a literature study by reviewing book references, journal articles and social media if necessary. From the data that has been collected, the next step is to analyze it so that conclusions can be easily drawn. The results show that Autism is a developmental disorder in children who are unable to communicate and express their feelings and desires. Usually this disorder is seen before the age of 3 years. People with Autism really need educational services that can accommodate, complete, the facilities and infrastructure they need, such as in inclusive schools. In inclusive schools, children with autism can learn independently and develop their ability to communicate and develop social interaction skills, namely communicating well with their peers. So that for people with autism, the role of inclusive schools is needed by handling, facilities and infrastructure in an effort to develop the development of autistic children.Keywords: Development, autism, early childhood